Do Obsoleto à Transformação - Reflexão Crítica sobre Arquitectura Industrial no Ginjal - Miguel Nuno Pereira Vinagre (2017)
This essay is the result of a critical reflection on industrial architecture, something I always saw from the windows of my house. The study object, Fábrica de Desestanho Virgílio Martins Correia and Armazéns Theotónio Pereira, is located in Ginjal, Almada. This work is based on a personal point of view about an obsolete territory in need of a transformation. This reflection is a journey that crosses a project. The project, which is divided in four chapters is arranged in a logical sequence in two volumes, resulting from a specific approach to an existing reality. At first, the study object is framed in space and time through an investigation of geographical and historical contexts. It's followed by the analysis of the contemporary use of the study object and the consequent definition of the program, culminating in an explanation of the transformations applied. These transformations, gathered in a second volume, are described through a series of surveys and photographs that describe the current state of ruin and a set of drawings, used to explain in detail the developed proposal. A set of references and objects are collected that intend to clarify the reader about the project. This way, one navigates between the chapters, aiming at a formal understanding of the place and the proposal, exploring a setup that responds to an investigation of theoretical-practical nature. The solution with two volumes allows one to roam through the texts and the drawings, the analysis and the interpretations, with the aim of creating an individual narrative, by subverting a fixed sequence. This cycle of studies is concluded with an exercise that retains a complex reality derived from a set of external factors that reinforce the presented solution and bring it closer to current practice.